Geospatial and Ethnic Mapping of Plasmodium Knowlesi Genetic Variants in Sabah - Daw Khin Saw Naing; Zaw Lin; Nor Amalina Emran; Yusof Hj Ibrahim; Tajul Ariffin Awang Mohd (Universiti Malaysia Sabah, 2014)
Plasmodium knowles;, an originally zoonotic malaria parasite is now increasingly recognized as a potentially virulent type of human malaria, particularly in South East Asia Naturally acquired human infections with P. knowlesi emerged either as single infection or associated with other human Plasmodium, across the Southeast Asia with the highest prevalence in the Malaysian Borneo. Sabah is the second largest state of Malaysia situated on the Borneo Island. And this simian parasite Plasmodium knowles; is a common cause of severe and fatal human malaria in Sabah, Malaysia This study focused on the P knowles; isolates of Sa bah principally on the blood samples of P knowles; malaria sent to the public health laboratory of Kota Kinabalu confirmed by Nested peR Assay. From the DNA samples of P knowlesi isolates, DNA sequencing was done to detect the genetic variants of P knowles; in different regions of Sa bah. The PCR - DNA sequencing of SSU r RNA gene of P. knowles; isolates points out that SNPs at continuous three nucleotide positions 278, 279 and 280 can produce the genotypic characteristics important from the epidemiological point of view. Although these genotypes are not consistent for each district of Sabah, these can help in epidemiological surveillance as only four genotypes are circulating in this area. For district specific genetic identity, genetic variations of the csp gene of P. Icnowlesi isolates should be attempted in the future studies.